A cartografia do relevo de áreas de sedimentação recente: O caso do litoral sul paulista - Cunha, Cenira Maria Lupinacci da [UNESP]; Souza, Tissiana de Almeida de [UNESP] (My University, 2010)
The coast environments were the first areas the man occupied in Brazil and they present, nowadays, high urbanization indexes. So, it's very important to analyze the environmental quality of those areas. The geomorphologic aspects are valuable for that analysis because they constitute the physical substrate on which such ant anthropic activities are developed. The cartography of geomorphologic features is essential to supply subsidies for the handling of coastal areas. However, the question about what proceedings are adequate to the geomorphologic cartography of recent sedimentation coastal lands is still in discussion by many authors. This article aims to compare two different technical proposals for mapping São Paulo's south coast, a sector that shows a great depositional complexity. The features related to recent sedimentation sectors were mapped because it's considered that they are necessary to understand the morphodynamic and, at the same time, they demonstrate difficulties in geomorphologic cartography standardization. Through the analysis of the produced maps it's possible to notice that the two proposals have positive aspects, but both need adaptations to cartographically demonstrate the geomorphologic complexity of São Paulo's south coast.

Os ambientes litorâneos foram as primeiras áreas ocupadas pelo homem no Brasil e apresentam, nos dias atuais, elevados índices de urbanização. Neste contexto, é de suma importância analisar a qualidade ambiental destas áreas. Para tal análise, os aspectos geomorfológicos são importantes por constituírem o substrato físico sobre o qual tais atividades antrópicas se desenvolvem. Assim, a cartografia das feições geomorfológicas é essencial para fornecer subsídios para o manejo das áreas litorâneas. Contudo, os procedimentos adequados para a cartografia geomorfológica dos terrenos litorâneos de sedimentação recente ainda é fruto de discussão visto que há diversos autores que tratam dessa questão. Dessa forma, o objetivo deste trabalho foi comparar duas propostas técnicas diferentes para o mapeamento do litoral sul paulista, setor que apresenta grande complexidade deposicional. Foram mapeadas as feições vinculadas aos setores de sedimentação recente, pois se considera que estes são essenciais para o entendimento da morfodinâmica e, concomitantemente, apresentam dificuldades de normatização da cartografia geomorfológica. Através da análise das cartas produzidas, pode-se constatar que as duas propostas apresentam aspectos positivos, contudo ambas necessitam de adaptações para demonstrar cartograficamente a complexidade geomorfológica do litoral sul paulista. Palavras-chave: cartografia geomorfológica, morfodinâmica, litoral, sedimentação recente.
The relief cartography of recent sedimentation areas: The sample of são paulo's south coast
Keywords: Coast; Geomorphologic cartography; Morphodynamic; Recent sedimentation; cartography; coastal zone; deposition; environmental quality; geomorphological mapping; human activity; morphodynamics; relief; sedimentation; substrate; urbanization; Brazil; Sao Paulo [Brazil]